Kecemasan Preoperasi pada Pasien di Unit One Day Surgery(ODS) - Usnadi, Udi; Rahayu, Urip; Praptiwi, Atlastieka (Jurnal Keperawatan 'Aisyiyah, 2019)
ODS (One Day Surgery) service is an innovation in surgical treatment in recent decades and is claimed to have many advantages. However, increased use of anesthetic drugs, pain management during postoperative, increased length of recovery or hospitalization, increased risk of infection and increased costs are complications that can result from poorly managed preoperative anxiety. This study aimed to identify anxiety preoperative ODS patients in Dr. Hasan Sadikin Bandung. This research used quantitative descriptive design with sample of 60 patients recruited by purposive sampling technique. Data collection used Spielberger State-Trait Anxiety Inventory (STAI: Y-6) instrument and APAIS (Amsterdam Preoperative Anxiety And Information Scale) are valid and reliable. Data analysis used descriptive statistics. The results showed that all respondents experienced preoperative anxiety with mean 53,94 (SD ± 9,38). Based on the source of preoperative anxiety, the preoperative anxiety picture associated with the mean operating procedure 5.65 (SD ± 1.94), anxiety concerning the mean anesthesia procedure of 5.37 (SD ± 1.83) and the anxiety associated with the need to obtain the mean information of 7.43 (SD ± 1.98). It can be concluded that all preoperative patients in ODS experience preoperative anxiety in relation to the need for information. It is recommended that hospitals improved the quality of providing information to patients and families by involving interdisciplinary teams, thereby improved the overall quality of ODS services and improved patient and family satisfaction. Keywords: Anxiety, One Day Surgery (ODS), Preoperative.